(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Long-term and short-term growth are affected by monetary policy. This study focuses on investigating monetary policy and its impact on the Indian economy. Central banks monitor the money supply to ensure price stability. The study uses gross domestic product (GDP) as the dependent variable and repo and reverse repo rates, unemployment rate, foreign direct investment and inflation as independent variables. These variables were used to show how completely dependent a country’s economy is. Various inputs were used to calculate GDP. The purpose of this study is to assess the efficiency of Indian monetary policy and the impact of certain financial instruments on the domestic economy.